긍정심리학과 신경생물학, 유전 - 강은호(Eun-Ho Kang) (Seuteureseu yeon-gu (Online), 2007)
Recent developments in neuroscience and genetics have suggested that there are biological bases in the field of positive psychology as well as pathology-oriented psychology and neuropsychiatry. However, psychologists, psychiatrists, and scientists have little knowledges of the biological process by which happiness, well-being, optimism, positive individual traits make people endure stress and enjoy better life. The author provides an outline of neuroscientific and genetic researches on the elements of positive psychology. (Korean J Str Res 2007;15:221∼225) KCI Citation Count: 5